Randomized double-blind placebo-controlled trial of perhexiline in heart failure with preserved ejection fraction syndrome. (November 2014) - Singh, Satnam; Beadle, Roger; Cameron, Donnie; Rudd, Amelia; Bruce, Maggie; Jagpal, Baljit; Schwarz, Konstantin; Brindley, Gemma; Mckiddie, Fergus; Lang, Chim; Dawson, Dana; Frenneaux, Michael
ABSTRACT : Recently heart failure with preserved ejection fraction (HFpEF) has emerged as a huge epidemic. Increasing evidence shows the role of energy deficiency in the pathophysiology of HFpEF. In the current study, we hypothesize that the use of metabolic modulator perhexiline would correct myocardial energy deficiency and improve exercise capacity and diastolic abnormalities in patients with this syndrome.